Pay It Forward? Law and the Problem of Restricted-Spending Philanthropy - Brian Galle (Washington University Law Review, 2016)
American foundations and other philanthropic giving entities hold about $1 trillion in investment assets, and that figure continues to grow every year. Even as urgent contemporary needs go unmet, philanthropic organizations spend only a tiny fraction of their wealth each year, mostly due to restrictive terms in contracts between donors and firms limiting the rate at which donations can be distributed. Law has played a critical role in underwriting and encouraging this buildup of philanthropic wealth. For instance, contributors can typically take a full tax deduction for the value of their contributions today, no matter when the foundation spends their money, and pay no tax on the investment earnings the organization reaps in the meantime. What, if anything, justifies public support for “restricted spending” charity? This Article offers the first comprehensive assessment of that question and supplies original empirical evidence on several key aspects of it. I argue that restricted spending sacrifices crucial information, leaves superior opportunities on the table, and on average transfers funds to times when they are less useful. While there is a place for large and long-lived philanthropic organizations in American society, that role does not require public support for restricted spending. As long as foundations can demonstrate their value to new donors, they will continue to thrive. I set out a series of policy recommendations aimed at better reconciling nonprofit law and the principles that justify it. I support my claims with new evidence drawn from a data set of over 200,000 firm-year observations of private foundations. For example, I find that foundations earn about twice as much money per year as in earlier studies funded by foundation-industry lobbyists and that they are growing three times faster than those earlier studies suggested. This finding implies that the law could require a much higher annual “payout” from foundations. I also find that new laws introduced in about a dozen states since 2006 have significantly slowed foundation spending in the enacting states. Last, I offer simulations of several policy proposals for making foundations more effective at fighting recessions.
Keywords: charity; restricted spending; philanthropy; corporations law